Mezzanine capital as a stimulant for sustainable regional growth - Dylewski, Marek (Kapitał mezzanine jako stymulanta zrównoważonego rozwoju regionów, 2014)
The issue of financing regional growth is of paramount importance as it pertains to both a region as a whole and to business entities that make up this region. The currently commencing new perspective of EU programming draws up new goals, introduces new logic in terms of intervention objectives and the ways of their financing. The purpose of this paper is to present the guidelines of the new logic of financing in the programming period in the years 2014–2020 together with the significance of mezzanine financing in creating sustainable regional and corporate development. The article presents an approach to sustainable development in the new logic of funding and mezzanine capital in the financing of environmental protection. It also dicusses the idea of funding by Polish Investments for Development as a new partner in the financing of investment in regions
Biblioteka Regionalisty, 2014, Nr 14, s. 15-26
Keywords: local development; the new programming period; the financing of development; mezzanine capital; finansowanie rozwoju; rozwój lokalny; kapitał mezzanine